1997
DOI: 10.1038/ki.1997.362
|View full text |Cite
|
Sign up to set email alerts
|

Mutation (677 C to T) in the methylenetetrahydrofolate reductase gene aggravates hyperhomocysteinemia in hemodialysis patients

Abstract: Hyperhomocysteinemia is frequent in hemodialysis patients and represents an independent risk factor for vascular disease in these patients. Elevated total homocysteine (tHcy) plasma levels can results from defective remethylation of Hcy to methionine due to decreased activity of the enzyme methylenetetrahydrofolate reductase (MTHFR). A genetic aberration in the MTHFR gene (677 C to T substitution) has been shown to result in reduced MTHFR activity. We tested the hypothesis that elevation of tHcy plasma levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
4
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 47 publications
8
62
4
7
Order By: Relevance
“…However, it could not be observed in other studies (31,32) , since Hcy concentration decreased in all genotypes. Another confounding factor that could affect the outcomes of Hcy-lowering therapy among patients on dialysis might be the dialysis procedure and membrane pore size.…”
Section: Studycontrasting
confidence: 73%
“…However, it could not be observed in other studies (31,32) , since Hcy concentration decreased in all genotypes. Another confounding factor that could affect the outcomes of Hcy-lowering therapy among patients on dialysis might be the dialysis procedure and membrane pore size.…”
Section: Studycontrasting
confidence: 73%
“…In individuals with healthy renal function, the T/T genotype causes only a 25% increase in tHcy concentration compared with persons with other genotypes (6 ), but in patients with end-stage renal disease undergoing maintenance dialysis, the T/T genotype causes a 40% to 100% increase in tHcy (7 ).…”
Section: © 2006 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Further studies demonstrated that the C/C genotype matched with low LPH-specific mRNA expression and low lactase activity in intestinal biopsies, suggesting primary adult hypolactasia, whereas the genotypes C/T and T/T matched with high LPH-specific mRNA expression and high lactase activity, strongly suggesting lactase persistence (7)(8)(9)(10)(11). A second described SNP, LPH G3 A Ϫ22018 , is thought to be only in linkage disequilibrium with the SNP C3 T Ϫ13910 (11 ).…”
Section: © 2006 American Association For Clinical Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The serum Hcy level was higher in patients with TT genotype than in those with other genotypes, and the relationship between Hcy and genotype was stronger in the low folate intake [9]. The frequency of the TT genotype was 13.7 % in a study of hemodialysis patients, and it was higher (23.8 %) in patients with a cardiovascular disorder, showing that the MTHFR polymorphism is an important factor that influences the serum Hcy level [10,11]. However, there have been only a few studies of Japanese patient with renal failure and hemodialysis patients, and the MTHFR C677T polymorphism has not been investigated in longterm hemodialysis patients.…”
Section: Introductionmentioning
confidence: 99%